The Adoption Level of Online E-Transportation Apps - Yosi Afandi, Endang Siti Astuti, Andriani Kusumawati, Yusri Abdillah (International Journal of Advanced Science and Technology, 2020)
Recently, the demand for mobility in Indonesia is very high, so it needs technology-based transportation innovation. Lately, transportation innovations developing in Indonesia are in form of online transportation application, these transportation applications are sought by many Indonesian because they greatly facilitate many activities of user or consumer. In previous studies, there has been no discussion about the adoption level of online transportation application, which tested and studied about the effect of self-efficacy and trust on perceived risk and its impact on usage intention of online e-transportation apps by using the TAM method. The TAM method can be used to provide an understanding of a person’s behavior in receiving technology. Therefore, this method is appropriate to be used in the research conducted so the effect of self-efficacy and trust can be found on perceived risk toward the acceptance of online e-transportation apps. Based on this research. The research, trust variable was the most dominant variable in influencing the use of online e-transportation apps compared to the self-efficacy and perceived risk variables. The self-efficacy variable was not dominant in influencing the usage intention of online e-transportation apps.